2012
DOI: 10.3390/s120302400
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Integrated Chip for Automatic Tracking and Positioning Manipulation for Single Cell Lysis

Abstract: This study adopted a microelectromechanical fabrication process to design a chip integrated with electroosmotic flow and dielectrophoresis force for single cell lysis. Human histiocytic lymphoma U937 cells were driven rapidly by electroosmotic flow and precisely moved to a specific area for cell lysis. By varying the frequency of AC power, 15 V AC at 1 MHz of frequency configuration achieved 100% cell lysing at the specific area. The integrated chip could successfully manipulate single cells to a specific posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Numerous researchers are working on developing a non-invasive separation device to characterize cells based on dielectric parameters 16 . DEP has been widely used in cell lysis research 17 and in characterisation of a variety of yeasts 18 and human cells, such as nerve cells 19 , platelets 20 , sperm cells 21 , cancer cells 22 , and leukaemia cells 23 . Many studies have been conducted to determine the dielectric properties of human whole blood 24 , T and B lymphocytes 25,26 , and erythrocytes 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers are working on developing a non-invasive separation device to characterize cells based on dielectric parameters 16 . DEP has been widely used in cell lysis research 17 and in characterisation of a variety of yeasts 18 and human cells, such as nerve cells 19 , platelets 20 , sperm cells 21 , cancer cells 22 , and leukaemia cells 23 . Many studies have been conducted to determine the dielectric properties of human whole blood 24 , T and B lymphocytes 25,26 , and erythrocytes 27 .…”
Section: Introductionmentioning
confidence: 99%
“…They observed cell lysis at a rate of 0.2 cells per second. Young et al . reported an on‐chip electrical lysis of single‐lymphoma cell at 80 % success rate and injection‐to‐lysis time of 60 s. Bahi and co‐workers trapped an array of single‐cells via on‐chip DEP (1 V) followed by lysis at 60 V potential.…”
Section: Single‐cell Lysismentioning
confidence: 99%
“…The cell traveled to aT -intersection where the high electric field (4 kV) ruptures the cell.T hey observed cell lysis at ar ate of 0.2 cellsp er second. Young et al [152] reported an onchip electrical lysis of single-lymphoma cell at 80 %s uccess rate and injection-to-lysis time of 60 s. Bahi and co-workers [153] trapped an array of single-cells via on-chip DEP (1 V) followed by lysis at 60 Vp otential. The method reported 100 %t rapping and lysing efficiency.H owever,t his method did not provide a way for separate collection of each single-cell lysates and all the extracted RNA was collected using ap ipette after lysis.…”
Section: Single-cell Lysismentioning
confidence: 99%
“…The authors found single cell lysing events occurring at a rate of 0.2 cells s-1. Young and co-workers 208 demonstrated a microfluidic device for EOF positioning and electrical lysis of a single lymphoma cell. Their method reported a success rate of 80% while taking approximately 60 seconds on average from cell injection to cell lysis.…”
Section: Sample Preparationmentioning
confidence: 99%